A Systematic Review on the Effects of Plant-Feeding by Omnivorous Arthropods: Time to Catch-Up With the Mirid-Tomato Bias? - Puentes, Adriana; Stephan, Jörg G.; Björkman, Christer (Frontiers in Ecology and Evolution, 2018)
Zoophytophagous (omnivorous) predators provide valuable pest control services, and offer an advantage over strict carnivores as plant-feeding enables survival during prey shortage. This putative advantage can potentially be their downside, as plant-feeding may entail damage that negatively affects plant growth/yield (i.e., the cost arising from of omnivore plant-feeding). Yet, benefits conferred by predatory services are usually thought to counterbalance any impact of plant damage. In this systematic review, our goal was to determine how often levels of omnivore damage and its consequences for plants (costs) are considered or quantified. We provide a synthesis of publication trends and findings on omnivore plant-feeding levels, plant injury variables, actual (if quantified) and potential effects on growth/yield, the type of study (lab, greenhouse) and the plants/omnivores most often examined. Our search revealed that measures of omnivore plant-feeding are occasionally reported, but seldom are the direct consequences of such damage also considered. Omnivore plant-feeding were reported in 57% of studies (53 of 93 full-text examined); within these, the majority (>80%) indicated moderate to high levels of plant-feeding. However, only 22% of reports (15 of 69) quantified the effects of omnivore-inflicted damage on plant performance. Of these 15 reports, a greater number found negative consequences for plants compared to those showing no effect (8 vs. 4; 3 with both), with consequences for yield relative to growth being more often evaluated (6 vs. 2). Overall, fruit/leaf injuries relative to stem/flower-feeding were most often examined, and lab/greenhouse experiments predominated. Tomatoes (Solanum lycopersicum) and the mirid Nesidiocoris tenuis were the most common species studied (34 and 14 reports, respectively). Our results indicate that costs to plants of omnivore-inflicted damage are often neglected. We argue that predatory benefits need to be simultaneously considered with plant-feeding effects to appropriately evaluate pest control services. Publication trends suggest that more studies are evaluating costs to plants, but a paradigm shift is still needed. Furthermore, we found that our understanding of plant-feeding and its effects is disproportionally based on studies examining tomato plants and its omnivorous biocontrol agents. To confirm the generality of findings thus far, other plant omnivore systems should be further considered.